SOCIAL CONDITIONS AND MATERNAL CONDUCTS IN THE PREVENTION AND MANAGEMENT OF INFANTILE DIARRHEA - Brena Shellem Bessa de Oliveira; Rhaiany Kelly Lopes de Oliveira; Jallyne Colares Bezerra; Francisca Mayra de Sousa Melo; Flávia Paula Magalhães Monteiro; Emanuella Silva Joventino (Universidade Federal do Paraná, 2017)
The aim was to characterize the social conditions, incidence of diarrhea, and maternal conducts in the prevention and management of this pathology. A descriptive study was undertaken with 385 mothers of children below five years of age, resident in the rural region of Ceará, in August - October 2015. Structured interviews were held, and the data were analyzed using descriptive statistics. It was ascertained that 79.7% of the houses had a septic tank; 71.1% used the public service as their water supply; 96.6% of the mothers washed their hands with soap and water; 52.7% of the children investigated had had diarrhea; and 91.2% of the mothers who mentioned offering home-prepared oral rehydration solution to their child prepared this inadequately. It was observed that maternal skills are essential for the children's well-being, and that it is important that the mothers should be provided with guidance and encouraged in relation to the prevention and treatment of diarrhea.